Research on the Selection Strategy of Green Building Parts Supplier Based on the Catastrophe Theory and Kent Index Method. (20th September 2016) - Luo, Zhenhua; He, Jian; Pan, Haize; Yang, Yiluan
Abstract : At present, the green building and housing industrialization are two mainstream directions in the real estate industry. The production of green building parts which combines green building and housing industrialization, two concepts, is to be vigorously developed. The key of quality assurance in the assembly project is choosing reliable and proper green building parts suppliers. This paper analyzes the inherent requirements of the green building, combined with the characteristics of the housing industrialization, and puts forward an evaluation index system of supplier selection for green building parts, which includes product index, enterprise index, green development index, and cooperation ability index. To reduce the influence of subjective factors, the improved method which merges Kent index method and catastrophe theory is applied to the green building parts supplier selection and evaluation. This paper takes the selection of the unit bathroom suppliers as an example, uses the improved model to calculate and analyze the data of each supplier, and finally selects the optimal supplier. With combination of the Kent index and the catastrophe theory, the result shows that it can effectively reduce the subjectivity of the evaluation and provide a basis for the selection of the green building parts suppliers.